Strategic framework for the development of coconut sector in the Kingdom of Tonga - Edgar Cocker, Jayasekhar Somasekharan, Tevita Lautaha; Maile Tahafitu Fa’ase’e, ‘Ilaisaane ‘Olivia Tu’itupou (Journal of Plantation Crops, 2017)
Strategic framework for the coconut sector is an important tool for small South Pacific countries such as Kingdom of Tonga in view of the time bound implementation of the strategic actions for revitalizing the sector. It is also important in terms of receiving the funds from developmental agencies, since the agencies assess the funding requests based on the planned framework developed in a convincing fashion. The present strategic framework for coconut sector of Tonga was evolved from a systematic study conducted through stakeholder discussions, focus group discussions, personal interviews, workshops/seminars and field demonstrations. Initially we have identified the sectoral challenges on production, trade and institutional facets. Subsequently, through the conduct of workshops, we have developed plausible strategies in a participatory mode wherein the concerns and suggestions of the stakeholders are very well reflected in the strategic framework developed. A National Coconut Development Council (NCDC) has been constituted which is a multi-agency body which is responsible for the implementation of the proposed strategic action plan in a time bound manner.